Papaya ringspot virus W infecting Luffa aegyptiaca in Cuba - Cabrera Mederos, Dariel; Giolitti, Fabian; Nome Docampo, Claudia; Bejerman, Nicolas Esteban; Portal, Orelvis (Springer, 2018)
Luffa aegyptiaca (sponge gourd) plants showing severe leaf mosaic and deformation symptoms were observed in Villa Clara, Cuba. Electron microscopy observations of leaf dip preparations revealed flexuous filamentous particles, which were identified as Papaya ringspot virus (PRSV) by ELISA test. PRSV was mechanically transmitted to healthy Cucurbita moschata plants. Sequence analysis of the RT-PCR product obtained from the capsid protein gene showed highest identity with other PRSV isolates from United States of America, Australia, Venezuela, Brazil, India and Cuba, ranging between 93.2–96.5% and 93.4–98.1% for nucleotide and amino acid sequences, respectively. Phylogenetic analysis showed two main clusters. Cluster I included isolates from the Americas-Australia group and India, including sponge gourd isolate, while the cluster II included isolates from China, Thailand and Taiwan. To our knowledge, this is the first report of PRSV-W infecting sponge gourd in Cuba.